2017
DOI: 10.1007/s00455-017-9794-2
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Preparation and Execution: Insights from a Delayed-Response Functional Magnetic Resonance Imaging (fMRI) Study

Abstract: The present study sought to elucidate the functional contributions of sub-regions of the swallowing neural network in swallowing preparation and swallowing motor execution. Seven healthy volunteers participated in a delayed-response, go, no-go functional magnetic resonance imaging study involving four semi-randomly ordered activation tasks: (i) "prepare to swallow," (ii) "voluntary saliva swallow," (iii) "do not prepare to swallow," and (iv) "do not swallow." Results indicated that brain activation was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 93 publications
4
24
0
Order By: Relevance
“…Ackermann and Riecker (2004) suggest that the insular contribution to speech motor control may reflect phylogenetic roots that have developed for motor coordination during swallowing. Accordingly, and in line with the authors' finding that insular activation was related to overt rather than silent speech, a more recent study found that swallowing-related insular activity was present during execution rather than preparation of swallowing (Toogood et al, 2017).…”
Section: Insula-interface To the "Inner Being"supporting
confidence: 78%
“…Ackermann and Riecker (2004) suggest that the insular contribution to speech motor control may reflect phylogenetic roots that have developed for motor coordination during swallowing. Accordingly, and in line with the authors' finding that insular activation was related to overt rather than silent speech, a more recent study found that swallowing-related insular activity was present during execution rather than preparation of swallowing (Toogood et al, 2017).…”
Section: Insula-interface To the "Inner Being"supporting
confidence: 78%
“…Swallowing-associated high γ bursts were observed in the region along the Sylvian fissure, including the subcentral area (BA 43) and the frontal operculum (BA 44). Previous studies have reported that swallowing activated the subcentral area (Martin et al, 2004;Toogood et al, 2017) and the frontal operculum (Dziewas et al, 2003;Lowell et al, 2008). In our study, swallowing-associated high γ bursts achieved a peak at the onset time of swallowing triggers, and subsequently, the high γ power decreased.…”
Section: Discussionsupporting
confidence: 66%
“…Swallowing is a coordinated physiological process, involving complex neuromuscular interactions (Ertekin and Aydogdu, 2003). Extensive research has shown that the swallowing network includes the brain regions of the primary sensorimotor system, supplementary motor area (SMA), insula, cingulate cortex, IFG, IPL, temporal lobe, precuneus, cerebellum, and brain stem (Hamdy et al, 1999a;Lang, 2009;Soros et al, 2009;Lima et al, 2015;Toogood et al, 2017). When any area of the swallowing network is damaged, dysphagia occurs (Domenech and Kelly, 1999;Gonzalez-Fernandez and Daniels, 2008).…”
Section: Introductionmentioning
confidence: 99%